Groundwater modelling in arid and semi-arid areas - Wheater, Howard; Mathias, Simon A.; Li, Xin (Cambridge University Press, 2010)
Arid and semi-arid regions face major challenges in the management of scarce freshwater resources under pressures of population, economic development, climate change, pollution and over-abstraction. Groundwater is commonly the most important water resource in these areas. Groundwater models are widely used globally to understand groundwater systems and to guide decisions on management. However, the hydrology of arid and semi-arid areas is very different from that of humid regions, and there is little guidance on the special challenges of groundwater modelling for these areas. This book brings together the experience of internationally leading experts to fill a gap in the scientific and technical literature. It introduces state-of-the-art methods for modelling groundwater resources, illustrated with a wide-ranging set of illustrative examples from around the world. The book is valuable for researchers, practitioners in developed and developing countries, and graduate students in hydrology, hydrogeology, water resources management, environmental engineering and geography
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Hydrologic models; Groundwater / Simulation methods; Arid regions; MODFLOW; Hydrogeologie; Trockengebiet; Grundwasserbildung; Infiltration; Grundwasser; Wasserhaushalt; Hydrogeochemie; Grundwasserstrom; Modellierung; Semiarides Gebiet